(untitled) (Global Journal of Computer Science and Technology, 2023)
This study examines how business intelligence BI tools are adopted in a higher education setting It made use of the theories of Diffusion of Innovation DOI Technology Readiness Index and Technology Acceptance Model TAM The psychometric features of the intended end-users were defined using TAM The technology- readiness of the users was assessed using TRI The DOI was used to describe the innovation itself The important factors for the adoption of the technology in this particular environment were identified through the examination of both quantitative and qualitative data To gain a better understanding of the socio-technical system as a whole a systems dynamics tool is presented to model the interaction of these elements along with the recommended interventions